Acceptability of a Mobile Health Exercise-Based Cardiac Rehabilitation Intervention: A RANDOMIZED TRIAL. Issue 5 (September 2015) - Pfaeffli Dale, Leila; Whittaker, Robyn; Dixon, Robyn; Stewart, Ralph; Jiang, Yannan; Carter, Karen; Maddison, Ralph
Abstract : BACKGROUND: Mobile technologies (mHealth) have recently been used to deliver behavior change interventions; however, few have investigated the application of mHealth for treatment of ischemic heart disease (IHD). The Heart Exercise And Remote Technologies trial examined the effectiveness of an mHealth intervention to increase exercise behavior in adults with IHD. As a part of this trial, a process evaluation was conducted. METHODS: One hundred seventy-one adults with IHD were randomized to receive a 6-month mHealth intervention (n = 85) plus usual care or usual care alone (n = 86). The intervention delivered a theory-based, automated package of exercise prescription and behavior change text messages and a supporting Web site. Three sources of data were triangulated to assess intervention participant perceptions: (1) Web site usage statistics; (2) feedback surveys; and (3) semistructured exit interviews. Descriptive information from survey and Web data were merged with qualitative data and analyzed using a semantic thematic approach. RESULTS: At 24 weeks, all intervention participants provided Web usage statistics, 75 completed the feedback survey, and 17 were interviewed. Participants reported reading the text messages (70/75; 93%) and liked the content (55/75; 73%). The program motivated participants to exercise. Several suggestions to improve the program included further tailoring of the content (7/75; 7%) and increased personal contact (10/75; 13%). CONCLUSIONS: Adults with IHD were able to use an mHealth program and reported that text messaging is a good way to deliver exercise information. While mHealth is designed to be automated, programs might be improved if content and delivery were tailored to individual needs. Abstract : A mixed-methods study was completed to assess the acceptability of an mHealth exercise intervention delivered to adults with ischemic heart disease. Participants found the technology easy to use and reported feeling motivated to exercise. The program might be improved through additional tailoring and personal contact.